Perception towards the Use of Self Service Technology in the New Age Banks - Saurabh; Taggar , Rashi; Giri , Sunil; Singh , Archana (Gyan Management Journal, 2009)
An increasing number of banks are using technology to deliver their regular service to the consumer. IT and Globalization has benefited the banking industry to become more customer oriented. IT in today’s Banks is more of a holistic approach towards designing and development of modern, robust, efficient, secure and integrated systems. But technology adopted by the banks is well adopted by the customers also depend on their perception and experience with these self services in banks. In thir study, the perception of people towards usage of self service options provided by the bank i.e. internet banking, phone banking, ATM’s and other automated services, etc is studied. A convenience sampling method was used and therefore 200 respondents were selected to be as the sample size specifically for the city of Jammu. Factor analysis was run on these 74 statements in order to observe the variability among observed random variable and reduce the set of variables in data set.